Alkaline-treated cocoa pod husk as adsorbent for removing methylene blue from aqueous solutions - Pua F.L.; Sajab M.S.; Chia C.H.; Zakaria S.; Rahman I.A.; Salit M.S. (2023)
In this study, cocoa pod husk (CPH) was used as adsorbent for removing methylene blue (MB) from aqueous solutions. Before the adsorption studies, the CPH was treated using sodium hydroxide (NaOH) to increase its adsorption capacity toward methylene blue (MB). The NaOH-treated CPH was characterized by SEM and FTIR analyses. Lignin was removed after the NaOH treatment, leaving higher accessible surface for adsorption. The adsorption performances of the CPH were investigated in terms of adsorption kinetics and isotherms under different conditions, i.e., pH, initial MB concentration, and temperature. Freundlich isotherm fits the adsorption experiment data better than that of Langmuir and Sips isotherms, suggesting the heterogeneous adsorption behavior of MB on the CPH. The maximum adsorption capacity of the NaOH-treated CPH toward MB is 263.9 mg/g. Pseudo-second order gives the better correlation to predict the kinetic process. The adsorption of MB on the NaOH-treated CPH was found to be endothermic and spontaneous. 2013 Elsevier Ltd All rights reserved.